Abnormal temperature-dependent photoluminescence characteristics of ReS2 nanowalls. (18th October 2021) - Xu, Xuejun; Hu, Xiaowen; Li, Xiaoli; Yang, Mingming; Liu, Jingtao; Guo, Qinglin; Wang, Ying; Liang, Baolai
Abstract: Two samples with [001] orientated rhenium disulfide (ReS2 ) nanowalls (NWs) grown above and in front of precursor (NH4 ReO4 ) by chemical vapor deposition were investigated. The temperature-dependent photoluminescence (PL) indicated that the PL peak exhibited linear blue-shift at a rate of ∼0.24 meV K −1 with increasing the temperature from 10 to 300 K, while the linewidth monotonically increased due to the exciton–phonon interaction. This abnormal blue-shift of PL emission energy, which is explained by a competition between the band gap shrinkage and the energy level degeneracy with respect to the increase of temperature and lattice constant, enables ReS2 NWs to possess great potential for development of thermal sensors. In addition, exciton localization effect in the ReS2 NWs from abundant edges and weak interlayer interaction was also observed to be related to the height and density of ReS2 NWs. These results not only enrich the understanding for exciton dynamics in ReS2 NWs, but also help to exploit ReS2 NWs for device applications.